Movements Execution in Amnestic Mild Cognitive Impairment and Alzheimer’s Disease - Rosolino Camarda; Cecilia Camarda; Roberto Monastero; Silvia Grimaldi; Lawrence K. C. Camarda; Carmela Pipia; Carlo Caltagirone; Massimo Gangitano (Behavioural Neurology)
We evaluated the relationship between motor and neuropsychological deficits in subjects affected by amnestic Mild Cognitive Impairment (aMCI) and early Alzheimer’s Disease (AD). Kinematics of goal-directed movement of aMCI and AD subjects were compared to those of age-matched control subjects. AD showed a slowing down of motor performance compared to aMCI and controls. No relationships were found between motor and cognitive performances in both AD and aMCI. Our results suggest that the different motor behaviour between AD and aMCI cannot be related to memory deficits, probably reflecting the initial degeneration of parietal-frontal circuits for movement planning. The onset of motor dysfunction in early AD could represent the transition from aMCI to AD.